Analisis Kerusakan Blower IDF pada PLTU PT PLN Indonesia Power UBP Holtekamp dengan Metode FMEA dan RCFA - Sendik Saputra; Eko Budi Utomo; M Hengki Riawan Putra (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
The Induced Draft Fan (IDF) blower is a critical component in the Holtekamp coal fired power plant system, responsible for regulating flue gas flow from boiler to the stack. Base on Pareto Loss from 2021-2025, IDF failures contributed to an average of 55% unit load reduction annually. The dominant failure modes identified were Breakage (crack/fracture) and Wear (abrasion/corrosion) on the fan impeller, which significantly effect plant reliability. This conditioning highlights the need for systematic analysis to trace the root causes of repeated failures. This study applies Failure Mode and Effect Analysis (FMEA) to determine failure modes using the Risk Priority Number (RPN) and Root Cause Failure Analysis (RCFA) with the 5 Why approach to identify recurring root causes. The results indicate that the main failure mode is material breakage with an RPN value of 336, causwed by improper material selection against abrasive, corrosive, dan high temperature conditions. Recommended solutions include implementing Life Cycle Management (LCM), reverese engineering for material enhancement, estabilishing monitoring checklists, and strengthening technical documentation and operational procedures. Keywords: IDF (Induce Draft Fan), Root Cause Failure Analysis (RCFA), Failure Mode and Effect Analysis (FMEA), Coal Steam Power Plant, Material Breakage